Pediatric otitis media in Fiji: Survey findings 2015. (June 2016) - Fang, Te-Yung; Rafai, Eric; Wang, Pa-Chun; Bai, Chiy-Huey; Jiang, Peng-Long; Huang, Shu-Nuan; Chen, You-Ju; Chao, Yi-Ting; Wang, Chen-Hsu; Chang, Chia-Hsiu
Abstract: Objective: Otitis media (OM), as a common infectious disease, is a major cause of hearing impairment among the general population. OM remains a major public health threat in the Pacific islands, but the risks of OM have not been thoroughly explored in this region. The objective of this study is to investigate the prevalence, clinical features, and quality-of-life impacts of OM in Fiji. Methods: In the medical service trip entitled "Healing and Hope – Taiwan Cathay Heart and Hearing Medical Mission to Fiji" (TCHHMMF), we conducted a cross-sectional OM survey study in Suva and Sigatoka areas (Korolevu, Cuvu, and Lomawai) in the summer of 2015. The otitis media – 6 (OM-6) was used to survey the OM-related quality of life. Results: In the 467 pediatric patients (aged 0–18 years old) screened, 13 (2.78%) have acute otitis media (AOM), 37 (7.92%) have otitis media with effusion (OME), and 19 (4.1%) have chronic otitis media (COM). Age (OR 0.53, 95% CI: 0.36–0.77) is a significant predictor of AOM, whereas male gender (OR 2.46, 95% CI: 1.13–5.37), smoke exposure (OR 2.81, 95% CI: 1.01–7.82), and concomitant chronic sinusitis (OR 6.05, 95% CI: 2.31–15.88) are significant predictors of OME. The mean OM-6 item scores are highest in caregiver concerns (3.8), physical suffering (3.7), and hearing loss (3.4) domains. Conclusion: OM is an important primary care disease in Fiji that remains under-served. It is critical to educate professionals, parents, and patients to detect and to improve care for OM.